Os horrores da Guerra: uma análise da memória entre dois relatos de sobreviventes do campo de extermínio de Auschwitz-Birkenau durante o Holocausto - Santos, Keli Cristina dos (2024)
When dealing with the concept of anti-Semitism, the 20th century is automatically present in social memory, this is not due to the fact that it was coined at this time, but rather, to the historical events that stand out in world historiography. More precisely, the Anti-Semitism has been present since ancient times, when the Jewish people remained in position of: the other, in society, based on the division of dominant and dominated peoples. O Anti-Semitism is also established in negative stereotypes coined from the idea of that the Jews would be involved in the death of Jesus Christ, based on the Christian religion Western, being considered the deicidal people, in this sense, the Jewish people became portrayed as to blame for social and economic ills over the centuries. In the first half of the 20th century, the Jewish community suffered several attacks in various parts of the world when discriminatory anti-Semitic laws were implemented brutally marking contemporary history, the subject of which will be exposed throughout this text. Above all, in Europe, the theories that have proliferated associated with stereotypes are often unfounded times harmed thousands of people, where each determinant was based on the extremism of a group, which has caused a legacy of suffering and a number exceptional number of victims was established in world history, together with the prejudice that remains rooted to this day, leading Jews to face attacks and discrimination in various parts of the world, highlighting the continued need to combat forms of intolerance.